Cortico-Hippocampal Brain Connectivity-Guided Repetitive Transcranial Magnetic Stimulation Enhances Face-Cued Word-Based Associative Memory in the Short Term - Wang, He; Jin, Jingna; Cui, Dong; Wang, Xin; Li, Ying; Liu, Zhipeng; Yin, Tao (Frontiers in Human Neuroscience, 2020)
Repetitive transcranial magnetic stimulation (rTMS) can be used to enhance the associative memory of healthy subjects and patients with Alzheimer’s disease. However, the question of where the stimulation should be applied is still unresolved. In a preliminary survey for an effective and feasible solution to this problem, we identified three representative rTMS targets using cortico-hippocampal connectivity calculated using resting-state fMRI (rs-fMRI) data from 80 young, healthy subjects: (1) the cortical area with the strongest connectivity across the whole cerebral cortical area; (2) the whole lateral parietal cortical area; and (3) the whole medial prefrontal cortical area. We then compared the short-term effects on associative memory, which was tested using face-cued word recall by applying rTMS to three identified targets in a single population of eight healthy adults. Each treatment lasted 2 d, associative memory performance was measured at four time points: before and after stimulation on the first day (baseline, Post 1); before and after stimulation on the second day (Post 2, Post3). Compared with baseline levels, 20 min of high-frequency rTMS delivered to target 2 or target 3 produced a significant increase in the mean accuracy of associative memory performance at the Post 3 time point alone (target 2, P=0.0035; target 3, P=0.0012). Compared with the sham conditions, significant increases in the mean associative memory performance were observed when high-frequency rTMS was delivered to target 2 (P=0.02) and target 3 (P=0.012), but not target 1 (P=0.1). Compared with baseline levels, 20 min of high-frequency rTMS delivered to target 3 produced a significant reduction in the mean reaction time of associative memory only at time points Post 1 (P=0.0464) and Post 3 (P=0.0477). Compared with the sham conditions, significant reductions in the mean reaction time of associative memory were observed when high-frequency rTMS was delivered to target 3 (P=0.006), but not target 1 (P=0.471) or target 2 (P=0.365). Our findings indicate that stimulation of the locations with the strongest cortico-hippocampal connectivity within the lateral parietal cortical or medial prefrontal cortical areas is effective in enhancing face-word-recall based associative memory in the short-term.